A knowledge transfer model on information technology outsourcing / Rozita Hanapi, Emelia Hj. Abdul Rahim and Sharidatul Akma Abu Seman - Hanapi, Rozita; Abdul Rahim, Emelia; Abu Seman, Sharidatul Akma (Research Management Institute (RMI), 2012)
IT outsourcing has become a trend among organization nowadays. Many organizations involve in outsourcing activities because they believe that certain business functions can be done effectively by an outside vendor. Generally, outsourcing refers to procurement of goods or services from an outside vendor (Lankford and Parsa, 1999). Kishore et al. (2003) defined IT outsourcing as "the contracting of various information systems functions such as managing of data centers, operations, hardware support, software maintenance, network, and even application development to outside service providers". According to Taylor(2005), IT outsourcing becomes popular due to many organizations have been forced to control their in-house IT operational cost and at the same time they feel the need to have high quality information systems that made them to consider IT outsourcing activities. In this context, a company can hire outside organization that has the specialize skills to provide IT outsourcing services to them if they do not want to use their internal resources to build or operate the IT or IS functions. Other than that, as difficulties in managing IT are arise, thus it become the reason for top management to hand over the job to someone outside the organization. If organization manages their IT outsourcing properly, they could reduce their operational cost significantly, they be able to transform fixed costs into variable costs, able to focus on core competencies and also have access to industry leading external competencies and expertise (Hoecht and Trott, 2006). In Malaysia, IT outsourcing has attracted at least RM11.4 billion (USD3 billion) of the global outsourcing business that is projected to be worth RM1.9 trillion (USD500 billion) by 2008 (Husnayati et al., 2006). The involvement includes from the private sector and also Malaysian government agencies.